The study of antimicrobial properties of immobilized fibrous N-chloro sulfonamides - V. N. Toropіn; Е. V. Surmasheva; L. I. Romanenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. The determination of antibacterial and antifungal action of nonwoven form of N-chloro sulfonamides immobilized on a polypropylene fiber with a graft copolymer of styrene and divinylbenzene.